Advancements in autonomous mobility of planetary wheeled mobile robots: A review - Zarei, Mahboubeh; Chhabra, Robin (Frontiers in Space Technologies, 2022)
Mobility analysis is crucial to fast, safe, and autonomous operation of planetary Wheeled Mobile Robots (WMRs). This paper reviews implemented odometry techniques on currently designed planetary WMRs and surveys methods for improving their mobility and traversability. The methods are categorized based on the employed approaches ranging from signal-based and model-based estimation to terramechanics-based, machine learning, and global sensing techniques. They aim to detect vehicle motion parameters (kinematic states and forces/torques), terrain hazards (slip and sinkage) and terrain parameters (soil cohesion and friction). The limitations of these methods and recommendations for future missions are stated.